2018
DOI: 10.1080/15592294.2018.1514853
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length and epigenetic-based mortality risk score: associations with all-cause mortality among older adults

Abstract: Telomere length (TL) has been established as a biomarker of aging and aging-related health outcomes, but showed only a weak or inconsistent association with all-cause mortality in previous epidemiological studies. Recently, an epigenetic 'mortality risk score' (MS) based on whole blood DNA methylation at 10 mortality-related CpG sites has been demonstrated to be strongly related to all-cause mortality at the population level. This study aimed to address the association between TL and this MS, and to assess and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Using data from residents of Detroit, we find that a recently developed epigenetic biomarker of mortality [27] is associated with summary measures of neighborhood characteristics constructed from objective measures of neighborhood characteristics which are indicative of neighborhood advantage/disadvantage based primarily on the quality of the built environment (Supplemental Table 2). The continuous epigenetic mortality score developed by Zhang et al [27] is a strong predictor of mortality, and in an independent validation study, a one unit increase was associated with a 2.64-fold increase (95% confidence interval, 1.98-3.52) in all-cause mortality risk [31]. We found that PC7, a principal component driven by neighborhood characteristics such as the number of abandoned Fig.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Using data from residents of Detroit, we find that a recently developed epigenetic biomarker of mortality [27] is associated with summary measures of neighborhood characteristics constructed from objective measures of neighborhood characteristics which are indicative of neighborhood advantage/disadvantage based primarily on the quality of the built environment (Supplemental Table 2). The continuous epigenetic mortality score developed by Zhang et al [27] is a strong predictor of mortality, and in an independent validation study, a one unit increase was associated with a 2.64-fold increase (95% confidence interval, 1.98-3.52) in all-cause mortality risk [31]. We found that PC7, a principal component driven by neighborhood characteristics such as the number of abandoned Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Recent advances in DNA array technology and data availability have allowed researchers to develop DNA methylation-based biomarkers for outcomes such as accelerated aging [29], chronic disease risk [30], and mortality risk [27,31]. For aging, there has been substantial work showing that DNA methylation age is accelerated by adverse environmental exposures [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, telomeres play a major part in cellular senescence [15] and might contribute signi cantly to the inherited background of human aging and longevity [16]. Aging results from a dynamic, complex, and multifactorial processes related to a decreased propofol dose by gradual accumulation of different types of cellular and molecular damage [17,18].TL demonstrated strong associations with propofol dose in our study, and be helpful for determining the propofol dose during aging as well as improving the safety of anesthesia.…”
Section: Discussionmentioning
confidence: 54%
“…We first derived a 10-CpG-based mortality risk score (MRscore) from a whole blood epigenome-wide association study (EWAS) of mortality [12]. The MRscore was shown to strongly predict all-cause and causespecific mortality, and to strongly correlate with other well-established aging indicators (such as telomere length, oxidative stress, frailty index, and the epigenetic clock), while outperforming these indicators in survival prediction [13][14][15]. The MRscore was first derived and validated in two large German cohorts, and its strong association with mortality has subsequently been confirmed in multiple large cohort studies from the United States, such as the Framingham Heart Study, the Women's Health Initiative, and the Normative Aging Study [11,16,17].…”
Section: Introductionmentioning
confidence: 99%